HUBUNGAN KEKERASAN DALAM RUMAH TANGGA YANG DILAKUKAN SUAMI PADA ISTRI DENGAN PERILAKU KEKERASAN IBU PADA ANAK (Studi di Wilayah Kelurahan Kaliawi Kecamatan Tanjung Karang Pusat Kota Bandar Lampung) - Diniyanti, Novita; Sidemen, I Gede (JURNAL SOSIOLOGI, 2012)
This study aimed to: 1) Describe the act of domestic violence committed husband and wife, 2) Violent behavior by wives of husbands have experienced kekarasan to the child, and 3) To clarify the relationship of domestic violence committed by husbands on wives mothers violent behavior in children Kaliawi Sub Sub Regional Centre Tanjung Karang Bandar Lampung. This type of research is explanatory (explanatory research), with a sample of mothers who had a husband and children who have experienced domestic violence in the Territory Kaliawi Village Center District Tanjung Karang Bandar Lampung (totaling 47 people). Questionnaire data collection techniques and documentation, while the data analysis carried out by statistical calculations using Spearman rank correlation test. The results showed that there is a correlation between domestic violence committed by the husband to his wife to violent behavior to the childs mother. The results of the analysis explains that the behavior of a wife who never get a husbands violence would have negative effects on maternal behavior in guiding their children everyday. If the violence of husbands against wives increased the acts of violence committed mothers to children tend to increase. Keywords: domestic violence, violence husband to wife, mother of violence on children